Analisis Determinasi ROE, DER, ROA Terhadap Harga Saham - Sandag, Eltie Christi; Durya, Ngurah Pandji Mertha Agung; Munizu, Musran; Dharmawan, Donny; Kusumaningati, Iip Dyah (Jurnal EMT KITA, 2024)
The purpose of this study is to determine the effect of ROE, DER, ROA on the Stock Price of Consumer Companies on the IDX. The research method used is a quantitative method with regression analysis, and the research sample is Consumer Companies on the IDX and consistently publishes financial reports from 2020 to 2023. Sampling was carried out using the purposive sampling method and data were analyzed using IBM SPSS version 25. The results of this study indicate that ROE, DER, ROA together have a significant effect on the stock price of Consumer Companies on the IDX. In general, the stock price of Consumer Companies on the IDX is influenced by the three independent variables, namely ROE, DER, ROA by 54 %.